2002
DOI: 10.1007/s00401-001-0493-5
|View full text |Cite
|
Sign up to set email alerts
|

Degenerative and vascular lesions of the brain have synergistic effects in dementia of the elderly

Abstract: The relative importance of vascular and Alzheimer's disease (AD) lesions, their interaction in the development of cognitive impairment and the very existence of mixed dementia induced by the potentiation of both mechanisms remain controversial. The aim of this study was to assess whether the patients with infarcts and lacunes have fewer plaques and tangles than those without vascular lesions, for similar severity of clinical dementia. We performed a prospective clinicopathological study in elderly patients of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
110
1
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(130 citation statements)
references
References 28 publications
16
110
1
3
Order By: Relevance
“…31 Moreover, in individuals with the same level of cognitive impairment, studies show that those with mixed pathologies have lower levels of AD pathology compared with individuals who have AD pathology alone. [32][33][34] Together, these investigations add further support to the notion that the effect of multiple pathologies may be additive or perhaps may interact in some way.…”
Section: Pathologic Evaluations the Uci Alzheimer's Diseasesupporting
confidence: 57%
“…31 Moreover, in individuals with the same level of cognitive impairment, studies show that those with mixed pathologies have lower levels of AD pathology compared with individuals who have AD pathology alone. [32][33][34] Together, these investigations add further support to the notion that the effect of multiple pathologies may be additive or perhaps may interact in some way.…”
Section: Pathologic Evaluations the Uci Alzheimer's Diseasesupporting
confidence: 57%
“…Furthermore, since an effect of lacunes on the rate of ERC atrophy was not detectable, our finding suggests that ERC atrophy rate may be more specific for AD pathology than hippocampal atrophy rate. However, AD patients have often co-existing cerebrovascular pathology, and further, AD and cerebrovascular disease may have an additional or even synergetic effect on dementia development [37,58]. Effect of lacunes on hippocampal atrophy rate but not ERC atrophy rate suggests that hippocampal atrophy rate may be a better marker for predicting the onset of dementia in subjects with cerebrovascular diseases than ERC atrophy rate.…”
Section: Discussionmentioning
confidence: 99%
“…Another risk factor for cognitive impairment, in addition to advanced age, is subcortical cerebral vascular disease, manifested as subcortical infarcts/lacunes and white matter hyperintensities (WMH) on MRI images [8,13,37,46,50,58]. A recent clinical study demonstrated that elderly individuals with silent brain infarcts were at greater risk for dementia and cognitive decline than elderly individuals without such lesions [53].…”
Section: Introductionmentioning
confidence: 99%
“…Clinicopathological studies have found that, for any level of cognitive deficit, the density of neuritic plaques and neurofibrillary tangles in the neocortex is Du 4 significantly lower in cases of AD mixed with cerebrovascular disease than in cases of AD without cerebrovascular disease [32,35,40], suggesting that cerebrovascular disease has effects in addition to AD pathology on cognition. Furthermore, Esiri et al found that vascular disease had a greater impact on cognitive performance at early stages of AD than at more advanced AD stages [14].…”
Section: Introductionmentioning
confidence: 99%